Frequency of radio consumption among the rural community in Sarawak - Alan, Ribka; Hassan, Md. Salleh; Bolong, Jusang; Osman, Mohd Nizam; Lepun, Philip; Kamarudin, Shafinah (Academia Industry Networks, 2020)
Radio is a communication channel that has been in use for a long time and was used to relay messages for those living in rural areas. The radio broadcasting medium has also been fully utilised to channel entertainment and information for the public, as well as a strategic channel for the ruling government. However, the level of information that is being broadcast through radio to people in rural areas is seen to be less effective due to lack of education. This paper aims at identifying the frequency of radio usage among the communities in rural areas for information search in order to increase their quality of life. This research involves respondents living in rural area of the Asap Koyan Resettlement in the district of Belaga, Sarawak. Research sampling was done randomly among 4,826 of the local population and 356 respondents were involved in this research. Research data was collected using survey forms and face-to-face interviews. Research findings show that the main information sought through the use of radio is political news and other information (entertainment programmes and urgent or emergency information dissemination). Research findings show that the daily radio listening frequency in a week is through Klasik Nasional FM at 33.4%. It is based on a research result that indicated that the allocated time to listen to the radio is more than two hours. It is hoped that the findings of this research could provide guidelines for research related to the rural communities in the future.